Factors associated with blood pressure control in hypertensive patients - Linares Cánovas, Lázaro Pablo; Pereda Rodríguez, Yoelys; Herrera Miranda, Guillermo Luís (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Introduction: the lack of control of blood pressure levels constitutes a serious health problem.Objective: determine the factors associated with blood pressure control.Method: observational, analytical, cross-sectional study, developed between 2021 and 2023, in a sample of 140 hypertensive patients, from office 59, of the Turcios Lima Polyclinic. The documentary review and the application of instruments allowed the obtaining of information that gave rise to the analyzed variables, using descriptive and inferential statistics methods.Results: 55,0 % of the patients did not have blood pressure control, which was associated with age (p